Efficacy of Grass and Concentrate Ratio on Milk Urea Nitrogen, Progesterone, and Pregnancy Status in Friesian Holstein - Hardaningtyas, Enggar; Mustofa, Imam; Madyawati, Sri Pantja; Rimayanti, Rimayanti; Safitri, Erma; Hermadi, Herry Agoes (Universitas Airlangga, 2022)
This study was conducted to know the influence of grass to concentrate ratio to milk urea nitrogen (MUN) level, progesterone level and pregnancy status in Friesian Holstein. A total of 18 dairy cows were randomly selected from the population. The cows were grouped based on feed and MUN and pregnancy. Milk sample collection was carried out once on the seventh day after estrus (D7) and tested with the Barthelot method for measuring urea nitrogen levels. Blood samples were taken three times, on the day of estrus (D0), seven days after estrus (D7), and twenty-two days after estrus (D22), and were tested using Immuno-Sorbent Assay (ELISA). Pregnancy examination was carried out at D90 after artificial insemination through rectal palpation. Based on the analysis, grass to concentrate ratio, progesterone level and MUN level showed no significant difference (p>0.05) but it showed significantly different on milk yield (p<0,05). Based on pregnancy status, progesterone level at D22 showed significantly different whereas at D0 and D7 showed insignificantly different. MUN level and grass to concentrate level also showed significantly different. It can be concluded that the ratio of grass and concentrate did not increase MUN level, progesterone level and pregnancy rate.